Pengaruh Governance terhadap Penerimaan Pajak Daerah - Saring Suhendro; Azolla Degita Azis; Gandy Wahyu Maulana Zulma (Universitas Batanghari Jambi, 2021)
This paper examines that good government governance has directly and moderating effect on local income tax determination. Using data from 33 province government in Indonesia for year 2008 and 2012, this research shows that good government governance is significant factor that improve local tax income directly and moderate variable. Good government governance strengthens positive correlation of per capita income and local tax income. While good government governance has not proven negative weakness of inflation and local tax.